L'exception de non-subrogation: l'influence de ses principes justificatifs sur sa mise en oeuvre - Parent, Alain (Université de Montréal, 2007)
À la lecture de l'article 2365 c.c.Q., le créancier et la caution ne peuvent pas percevoir les droits et les libertés que ce texte concrétise à leur encontre ou à leur profit. Pour pallier ce problème, les auteurs et la jurisprudence ont alors laissé place à leur imagination afin de tenter de classifier cette disposition à l'intérieur d'institutions juridiques éprouvées, le tout en vue de démythifier le contenu de la règle de droit. Pour notre part, nous considérons que l'exception de non-subrogation est une notion originale en soi, qui trouve sa source à l'intérieur même de son institution. La thèse que nous soutenons est que l'exception de non-subrogation, mode de libération qui a pour mission de combattre le comportement opportuniste, cristallise l'obligation de bonne foi en imposant implicitement au créancier une obligation de bonne subrogation. Tout manquement du créancier à cette obligation a comme conséquence de rendre le droit de créance du créancier irrecevable à l'égard de la caution devant les tribunaux. Ce précepte éclaircit le contexte de l'article 2365 C.c.Q. et, par le fait même, il permet de délimiter le contour de son domaine et de préciser ses conditions d'application. L'exception de non-subrogation est un mécanisme juridique qui date de l'époque romaine. Elle est maintenant intégrée dans presque tous les systèmes juridiques du monde, tant en droit civil qu'en common law. Dans la législation québécoise, elle s'est cristallisée à l'article 2365 C.c.Q. Il s'agit d'une disposition d'ordre public qui ne peut être invoquée que par la caution. Son application dépend du cumul de quatre conditions: 1) le fait du créancier; 2) la perte d'un droit subrogatoire; 3) le préjudice de la caution; 4) le lien causal entre les trois derniers éléments. Lorsque ces quatre conditions sont remplies, la caution est libérée de son engagement dans la mesure du préjudice qu'elle subit. Article 2365 of the Civil Code of Quebec ("C.C.Q.") states that the creditor and the surety cannot claim rights and liberties that the text secures for or against them. To deal with this problem, the authors and authorities gave free reign to imagination in an attempt to categorize this provision within recognized legal institutions and thereby demythicize the content of the rule of law. We are of the opinion that the non-subrogation exception is in itself an original concept that arises from within its institution. We believe that the non-subrogation exception, a discharge mode which aims at fighting opportunistic behaviour, crystallises the duty of good faith by implicitly imposing upon the creditor the obligation of subrogation. The creditor's failure to comply with this obligation will result in his right to claim in respect of the surety not being receivable in court. This throws some light on the context of Article 2365 C.c.Q., defines its boundaries and clarifies its applicability. The non-subrogation exception is a legal mechanism that goes back to Roman times. ft has now been incorporated into both civil and common law in almost ail legal systems in the world. In Quebec legislation, it falls under Article 2365 C.C.Q. It is a public order provision that only the surety can cite. The enforcement of this provision is subject to the following conditions: 1) the act of the creditor; 2) the loss of a subrogatory right; 3) the surety's prejudice; 4) the causal link between the three. When these conditions are fulfilled, the surety is released from his obligation to the extent of the prejudice he has suffered.
Keywords: Analyse économique du droit; Article 2365 c.c.Q.; Cautionnement; Civil law; Droit civil; Economic analysis of law; Exception de non-subrogation; Nonsubrogation; Source des obligations; Sources of obligations; Suretyship

A integração econômica como estratégia de desenvolvimento do continente africano: proposta de fusão entre a Comunidade Econômica do Estados da África Ocidental (CEDEAO) e a União Econômica e Monetária da África Ocidental (UMEOA) - Fernandes, Joel Aló (Universidade Federal de Santa Catarina, 2007)
Esta pesquisa tem por objetivo abordar a questão do processo de integração econômica dos Estados da África, como estratégia para o desenvolvimento do continente africano. A integração de Estados em blocos econômicos teve seu marco com a criação das Comunidades Européias nos anos 50 do século XX. Países europeus decidiram depois da Segunda Guerra Mundial agrupar-se (em processos políticos e econômicos) para evitar possíveis novas guerras e fortalecer suas economias destruídas por tais conflitos. A integração européia passou a servir de exemplo e modelo para as experiências de cooperação nos outros continentes. Na África, os Estados começaram a se aproximar depois da sua independência política no final dos anos 50 e início da década de 60, como forma de conjugar esforços para a libertação dos territórios que ainda se encontravam sob o jugo colonial, buscando também a libertação econômica dos territórios independentes. Nesse sentido, o presente estudo confere ênfase ao tema dos blocos econômicos da África Ocidental, destacando a importância da fusão entre a Comunidade Econômica dos Estados da África Ocidental (CEDEAO) e a União Econômica e Monetária da África Ocidental (UEMOA), com a finalidade do estabelecimento da Comunidade Econômica Africana.

Le principe « compétence-compétence » dans le contentieux maritime - Niviere, Marie (Université Paul Cézanne Aix-Marseille 3, 2007)

Analyse et exploitation de l'Etat C10b - Sawadogo, Pegwendé Moïse (Institut International des Assurances (IIA), 2007)

Small economies and their development in the Multilateral Trade System: correlation between economic and political environment and trade performance of small economies - Tiemeni, Thierry Galani (University of the Western Cape, 2007)
At the heart of this study is the topic of small economies in the Multilateral Trade System (MTS). The study examines the World Trade Organisation’s (WTO) legal framework and policy objectives in order to develop a comprehensive definition of small economies as a group of WTO members with specific needs. Particular attention is given to the determination of the specific characteristics of small economies, as well as the issues and constraints they are facing in the MTS. The study explores solutions proposed in order to tackle the constraints to the effective integration of small economies in the MTS, with specific reference to the policy reasoning of small economies. More importantly, the study explores the impact of the size factor, which is certainly not only a burden on the growth and development perspectives of the considered entity, but which may also become an advantage and promotes the trade performance of a small economy. Hypotheses are then made relating to the relevance of the economic and political environments in the determination of a successful (or not) integration, and participation, of a small economy in the MTS. A crucial argument developed is that the differences observed between countries sharing similar characteristics of smallness, vulnerability and remoteness/landlockedness, illustrates the fact that what ultimately matters is the interplay of factors related to the economic and political environments, the effect of which is to promote or constrain (depending on the case) successful integration of the small economy in the MTS.
https://hdl.handle.net/10566/18256
Keywords: Committee on trade and development; Developed countries; Economic environment; Multilateral trade system; Political environment; Small and vulnerable economy; Small economies; Trade performance; WTO; World Trade Organization